(8q-5)(6q-1)=0

Simple and best practice solution for (8q-5)(6q-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8q-5)(6q-1)=0 equation:


Simplifying
(8q + -5)(6q + -1) = 0

Reorder the terms:
(-5 + 8q)(6q + -1) = 0

Reorder the terms:
(-5 + 8q)(-1 + 6q) = 0

Multiply (-5 + 8q) * (-1 + 6q)
(-5(-1 + 6q) + 8q * (-1 + 6q)) = 0
((-1 * -5 + 6q * -5) + 8q * (-1 + 6q)) = 0
((5 + -30q) + 8q * (-1 + 6q)) = 0
(5 + -30q + (-1 * 8q + 6q * 8q)) = 0
(5 + -30q + (-8q + 48q2)) = 0

Combine like terms: -30q + -8q = -38q
(5 + -38q + 48q2) = 0

Solving
5 + -38q + 48q2 = 0

Solving for variable 'q'.

Factor a trinomial.
(1 + -6q)(5 + -8q) = 0

Subproblem 1

Set the factor '(1 + -6q)' equal to zero and attempt to solve: Simplifying 1 + -6q = 0 Solving 1 + -6q = 0 Move all terms containing q to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -6q = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -6q = 0 + -1 -6q = 0 + -1 Combine like terms: 0 + -1 = -1 -6q = -1 Divide each side by '-6'. q = 0.1666666667 Simplifying q = 0.1666666667

Subproblem 2

Set the factor '(5 + -8q)' equal to zero and attempt to solve: Simplifying 5 + -8q = 0 Solving 5 + -8q = 0 Move all terms containing q to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -8q = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -8q = 0 + -5 -8q = 0 + -5 Combine like terms: 0 + -5 = -5 -8q = -5 Divide each side by '-8'. q = 0.625 Simplifying q = 0.625

Solution

q = {0.1666666667, 0.625}

See similar equations:

| 16-7x=5x-2 | | -5+15=7x+14 | | 50=8x+3 | | 4x-2x+6=4+5x+1 | | y=21-2y | | 15+6x=2+-7x | | (3s-4)(s+5)=0 | | 7(b-2)=-34+2b | | 3+2lnx=5 | | 9y+1=2y+1 | | 2u(4u-3)=0 | | lx-8l=4 | | -x+38=-4(1-x)+2 | | x+(x-48660)=298710 | | 125=P*.04*2 | | tx+2t+hx+2h=0 | | 2m+3m=15 | | 6x+2-8=0 | | (3f+2)(f-2)=0 | | AX-D+BX=C | | g(x)=2ln(x)+3ln(x+4) | | -2x+10=-5x+1 | | 2(3-4x)+10=32-5x+7 | | (x-1)(x+3i)(x-3i)=equation | | 9=-4r-5r | | 12n=-288 | | 3x(5-3a)+5=2x-a | | M-42=14 | | -8k=48 | | 2300=P*.075*10 | | 4000=P*.03*4 | | (x+3)(x+2)(x-(1-i))=equation |

Equations solver categories